A fair non-repudiation framework for data integrity in cloud storage services. (1st January 2013) - Feng, Jun; Chen, Yu
Data storage is one of the most profitable applications on the cloud computing platforms. Although a transparent service model provides more flexibility and convenience, it may be subject to the loss of data integrity. Our study revealed vulnerability in some commercial cloud storage services, which potentially will lead to disputation between client and service provide or among multiple uses. In this paper, we propose a framework that supports a fair data transmission procedure without the risk of disputation. A basic two-party non-repudiation (TPNR) protocol and an advanced multi-party non-repudiation protocol (MPNR) are proposed. Rationales behind the new protocol's design and its working modes are presented in detail. We also discuss its robustness in the face of typical malicious network attacks.